GREEN SKILLS FOR INDEPENDENT AUDITORS: RESPONDING TO SPECIAL ECONOMIC ZONES AND SUSTAINABILITY CHALLENGES - Sugeng Riadi; Nadia Oktazen; Dahyang Ika Leni Wijayani (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2026)
In the context of SEZs and sustainable development, auditors face the challenge of integrating green skills into traditional audit practices, with financial competency dominating but insufficiently addressing environmental and social impacts. The study aims to explore the key green skills required by auditors to effectively assess and recommend on environmental-social impacts. This phenomenological qualitative study involved in-depth interviews with auditors from four major public accounting firms in Batam, analysed using NVivo software. Twelve key green skills have been identified, covering financial competence as a foundation, operational-managerial, effective communication and monitoring, engineering understanding, basic technical skills, scientific literacy, and specific managerial areas. Analytical procedures are also implicitly vital. These results enrich the auditor green skills framework; practically, auditors must integrate traditional competencies with these green skills for sustainable KEK audits.